Association of APOE ε4/ε4 with fluid biomarkers in patients from the PUMCH dementia cohort - Shang, Li; Dong, Liling; Huang, Xinying; Wang, Tianyi; Mao, Chenhui; Li, Jie; Wang, Jie; Liu, Caiyan; Gao, Jing (Frontiers in Aging Neuroscience, 2023)
Background Apolipoprotein-E (APOE) ε4 is a major genetic risk factor for Alzheimer’s disease (AD). Current studies, which were mainly based on the clinical diagnosis rather than biomarkers, come to inconsistent conclusions regarding the associations of APOE ε4 homozygotes (APOE ε4/ε4) and cerebrospinal fluid (CSF) biomarkers of AD. In addition, few studies have explored the associations of APOE ε4/ε4 with plasma biomarkers. Therefore, we aimed to investigate the associations of APOE ε4/ε4 with fluid biomarkers in dementia and biomarker-diagnosed AD. Methods A total of 297 patients were enrolled. They were classified into Alzheimer’s continuum, AD, and non-AD, according to CSF biomarkers and/or β amyloid PET results. AD was a subgroup of the AD continuum. Plasma Amyloid β (Aβ) 40, Aβ42, glial fibrillary acidic protein (GFAP), neurofilament light chain (NFL), and phosphorylated tau (P-tau)181 were quantified in 144 of the total population using an ultra-sensitive Simoa technology. We analyzed the associations of APOE ε4/ε4 on CSF and plasma biomarkers in dementia and biomarker diagnosed AD. Results Based on the biomarker diagnostic criteria, 169 participants were diagnosed with Alzheimer’s continuum and 128 individuals with non-AD, and among the former, 120 patients with AD. The APOE ε4/ε4 frequencies were 11.8% (20/169), 14.2% (17/120), and 0.8% (1/128) in Alzheimer’s continuum, AD and non-AD, respectively. Only CSF Aβ42 was shown to be decreased in APOE ε4/ε4 carriers than in non-carriers for patients with AD (p = 0.024). Furthermore, we did not find any associations of APOE ε4 with plasma biomarkers of AD and non-AD. Interestingly, we found that in non-AD patients, APOE ε4 carriers had lower CSF Aβ42 (p = 0.018) and higher T-tau/Aβ42 ratios (p < 0.001) and P-tau181/Aβ42 ratios (p = 0.002) than non-carriers. Conclusion Our data confirmed that of the three groups (AD continuum, AD, and non-AD), those with AD had the highest frequency of APOE ɛ4/ɛ4 genotypes. The APOE ɛ4/ɛ4 was associated with CSF levels of Aβ42 but not tau for AD and non-AD, suggesting that APOE ɛ4/ɛ4 affected the Aβ metabolism of both. No associations between APOE ε4/ɛ4 and plasma biomarkers of AD and non-AD were found.